Antioxidant‐related catalase CTA1 regulates development, aflatoxin biosynthesis, and virulence in pathogenic fungus Aspergillus flavus. (15th April 2020) - Zhu, Zhuo; Yang, Mingkun; Bai, Youhuang; Ge, Feng; Wang, Shihua
Summary: Reactive oxygen species (ROS) induce the synthesis of a myriad of secondary metabolites, including aflatoxins. It raises significant concern as it is a potent environmental contaminant. In Aspergillus flavus ., antioxidant enzymes link ROS stress response with coordinated gene regulation of aflatoxin biosynthesis. In this study, we characterized the function of a core component of the antioxidant enzyme catalase (CTA1) of A . flavus . Firstly, we verified the presence of cta1 corresponding protein (CTA1) by Western blot analysis and mass‐spectrometry based analysis. Then, the functional study revealed that the growth, sporulation and sclerotia formation significantly increased, while aflatoxins production and virulence were decreased in the cta1 deletion mutant as compared with the WT and complementary strains. Furthermore, the absence of the cta1 gene resulted in a significant rise in the intracellular ROS level, which in turn added to the oxidative stress level of cells. A further quantitative proteomics investigation hinted that in vivo, CTA1 might maintain the ROS level to facilitate the aflatoxin synthesis. All in all, the pleiotropic phenotype of A . flavus CTA1 deletion mutant revealed that the antioxidant system plays a crucial role in fungal development, aflatoxins biosynthesis and virulence.